The Impact of Standard Labor Relations On Inequalities - Kostov, Lyuboslav (Research Papers, 2021)
The problem of the connection between inequalities and the change in the labor relations in the OECD countries for the period 1980 - 2018 is studied. As a main conclusion from it can be stated that one of the reasons for the increase of inequalities is the change of standard labor relations, such as: 1) a decrease in the trade union density, 2) an increase in self-employment and 3) an increase in hourly employment.
Keywords: Technological progress; Labor market; Inequalities